Study of mucoadhesive microsphere of pirfenidone for nasal drug delivery - Kashikar, Vrushali; Dhole, Shashikant; Kandekar, Ujawala; Khose, Prachi (Asian Journal of Pharmaceutics (AJP), 2014)
The present research work involves formulation development and evaluation of nasal mucoadhesive microsphere in view to, improve bioavailability and reduce dosing regimen. Microspheres were prepared by spray drying and cross-linking method using chitosan and HPMC K4M, using 32 central composite design. Microspheres were evaluated for particle size, drug content, swelling ability, and percentage yield. Compatibility was checked by doing Fourier transform infrared spectroscopy and Differential scanning calorimetry study. The polymorphism and particle shape were studied by X-ray diffraction and scanning electron microscopy. The average particle size of spray-dried and cross-linked formulations were found in the range between 20-50 Î¼m and 30-60 Î¼m with percent mucoadhesion in the range of 80%-90% and 60-70%, respectively. In vitro drug release was found to be proportional to drug to polymer ratio. In vitro drug release for optimized formulation, that is, (F1), for spray-drying method and cross-linking method was found to be 88.73% and 70.93% at the end of 6 h, respectively. Release of drug from microspheres followed non-Fickian diffusion kinetics. Ex vivo studies were performed with sheep nasal mucosa for mucoadhesion, histopathological study, and drug permeation. The histopathological study indicates nonirritant nature of microsphere. The microspheres were found to be stable at accelerated storage conditions for 1 month, as per International Conference of Harmonisation guidelines.